Counter-discourse of Islamic epistemology in the non-formal madrasahs in Malaysia - Kushimoto, Hiroko (Future Academy, 2018)
This paper aims to describe the nature of contemporary discourses on Islamic Epistemology. Islamic epistemology has gone through a reconstruction through the process of development of modern education system. While many contemporary Muslim scholars had tried to recover the "true" epistemology in Islam, the personal epistemology among the ordinal Muslims has rarely been discussed empirically. This study aims to fill the gap by identifying the nature of the contemporary Muslim’s epistemology through an analysis of counter-discourse based on the dimensions of personal epistemology. A series of field research was conducted in two non-formal Islamic schools (madrasahs) in Kuala Lumpur and Terengganu between 2010 and 2016. The nature of epistemology in the madrasah can be explained in comparison with the four dimensions: (1) peers, not only the teachers, are important “source of knowledge” ( Schommer, 1990) (2) but that is true only when people also have a trust in the traditional authority. Learning should take a long time as opposed to the belief in (3)"quick learning” ( Schommer & Dunnell, 1994) and in relation to the dimension of (4) “certainty of knowledge” (M. Schommer, 1990), knowledge is static but it should be reached through a process of construction of meaning. It is also found that in addition to the four dimensions, a dimension of (5) learning as a process of moral development should be considered to analyze the nature of Muslim discourse of epistemology.